MODEL PERTANIAN ORGANIK BERBASIS TANAMAN CEPAT PANEN DAN TOGA UNTUK KEMANDIRIAN PANGAN DAN PENGENDALIAN PENYAKIT PASCA BANJIR DI DESA PAYA UDANG KECAMATAN SERUWAY KABUPATEN ACEH TAMIANG - Mulia Safrida Sari; Muna Aulia Tiba; Muhammad Irfan; Selvia Williadani; Attariq Syah; Kasmiriati Br Harahap; Bustanul Akmal Putra (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2023)
Disease and food insufficiency are serious problems faced by community at the post-flood in Paya Udang Village, Seruway District, Aceh Tamiang Regency. To overcome these problems, a community service program was carried out in the form of making an organic farming model based on quick-harvest crops and toga plants. This program aims to increase local food production, food independence, and post-flood disease control through the application of sustainable organic farming practices. Fast-harvest crops such as spinach, kale, and cassava were chosen because they can provide quick results and meet the food needs of the community. Toga plants such as lemongrass were also introduced as a natural mosquito repellent and an effort to prevent mosquito-borne diseases. The program involves the active participation of the community, farmer groups, and the KKN team in the process of land clearing, soil preparation, planting, plant maintenance, and organic pest control. Through training, counseling, and mentoring, the community's knowledge and skills in organic farming are improved. The results of this program include increased local food production, diversified food consumption, increased food self-sufficiency, and post-flood disease risk control. In addition, the program also provides recommendations for policy development that supports organic farming and food sustainability at the local and national levels.